Efektivitas Program Operasi Pasar Murah di Kota Batam Tahun 2024 - Putri Rini Situmeang; Bismar Arianto; Rizky Octa Putri Charin (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
Batam City, as an industrial hub in the Riau Islands Province, plays a vital role in the region’s economic growth. However, a surge in inflation can affect investment interest, as investors tend to avoid areas with economic uncertainty. One of the main contributors to inflation in Batam is the food component, which experiences high demand, especially during certain periods such as religious holidays and the arrival of international tourists. Batam, which is not a food-producing area, faces significant challenges in meeting agricultural needs and currently remains dependent on supplies from outside the region. Geographic constraints, such as inefficient logistics, weather disruptions, and institutional weaknesses in the food sector, further aggravate inflation control efforts. In addition, hilly terrain and less fertile land limit the types of crops that can be cultivated, making food price stability critically important. This study aims to evaluate the effectiveness of the Low-Cost Market Operation Team Program (Tim Operasi Pasar Murah) in Batam City in 2024. The method used is Sequential Explanatory Design with a mixed-methods approach. Quantitative findings indicate that the average success rate of the program is 85.93%, with a target achievement rate of 90.12% and a satisfaction level of 86.11%. Qualitative results suggest that the policy of conducting low-cost market operations has been appropriate and carried out by authorized institutions, with strong collaboration between the government and the private sector. The program has succeeded in maintaining price stability ahead of the fasting month and Eid al-Fitr, receiving positive responses from the community and demonstrating good internal coordination. In conclusion, the low-cost market operation program in Batam City has been effective in curbing inflation before the fasting month and Eid al-Fitr. However, for comprehensive inflation control, relying solely on this program is insufficient. Additional strategies are needed to ensure sustainable food price stability.